Improved hybrid de novo genome assembly and annotation of African wild rice, Oryza longistaminata, from Illumina and PacBio sequencing reads. Issue 1 (20th March 2020) - Li, Wei; Li, Kui; Zhang, Qun‐jie; Zhu, Ting; Zhang, Yun; Shi, Cong; Liu, Yun‐long; Xia, En‐hua; Jiang, Jian‐jun; Shi, Chao; Zhang, Li‐ping; Huang, Hui; et al.
Abstract: African wild rice Oryza longistaminata, one of the eight AA‐ genome species in the genus Oryza, possesses highly valued traits, such as the rhizomatousness for perennial rice breeding, strong tolerance to biotic and abiotic stresses, and high biomass production on poor soils. To obtain the high‐quality reference genome for O. longistaminata we employed a hybrid assembly approach through incorporating Illumina and PacBio sequencing datasets. The final genome assembly comprised only 107 scaffolds and was approximately ∼363.5 Mb, representing ∼92.7% of the estimated African wild rice genome (∼392 Mb). The N50 lengths of the assembled contigs and scaffolds were ∼46.49 Kb and ∼6.83 Mb, indicating ∼3.72‐fold and ∼18.8‐fold improvement in length compared to the earlier released assembly (∼12.5 Kb and 364 Kb, respectively). Aided with Hi‐C data and syntenic relationship with O. sativa, these assembled scaffolds were anchored into 12 pseudo‐chromosomes. Genome annotation and comparative genomic analysis reveal that lineage‐specific expansion of gene families that respond to biotic‐ and abiotic stresses are of great potential for mining novel alleles to overcome major diseases and abiotic adaptation in rice breeding programs. This reference genome of African wild rice will greatly enlarge the existing database of rice genome resources and unquestionably form a solid base to understand genomic basis underlying highly valued phenotypic traits and search for novel gene sources in O. longistaminata for the future rice breeding programs.